Formação inicial de professores: as TDIC nos currículos - Mantoan, João Paulo Buraneli (2021)
This research proposes to investigate the curricular organization of initial teacher training, with regard to the use of TDIC as an instrument of formative guidance, in line with the contemporary needs of the digital society. Its objectives are: (1) to survey all courses Degree in Pedagogy offered in the city of São Paulo with grades 4 and 5 through the e-MEC portal. (2) Analyze curricular matrices, surveying the disciplines related to the use of technologies. (3) Check how the curricular matrices of the Pedagogy Degree course describe the work to be performed with the Digital Technologies of Information and Communication, in the initial training of the academics of the respective course. A documentary research was carried out, using a qualitative approach. The need to reflect on the treatment of TDIC in the initial training of Pedagogy students is related to the creation of interactive learning spaces, as well as to stimulate new ways of teaching, learning and interacting with knowledge through different languages. The data collection showed that 11 higher education institutions in the city of São Paulo concept 4 and 5 and that offer disciplines related more directly to the theme of technologies, among the HEIs raised on the e-Mec platform. There is the offer of curricular components that deal with technologies in their curricula. They were identified in the titles of the curricular components, through words related to contemporaneity, which emerged from the observation of the nomenclature. It is worth noting the lack of publication of the menus and pedagogical proposals of most of the institutions surveyed, which made it difficult to look more deeply at the set of disciplines and understand whether technologies permeate the other themes of the curriculum